2003
DOI: 10.1002/art.11237
|View full text |Cite
|
Sign up to set email alerts
|

Increased apoptotic neutrophils and macrophages and impaired macrophage phagocytic clearance of apoptotic neutrophils in systemic lupus erythematosus

Abstract: Objective. To evaluate whether patients with systemic lupus erythematosus (SLE) have a higher rate of apoptosis in and secondary necrosis of polymorphonuclear neutrophils (PMNs) and macrophages compared with controls; to compare the rate of macrophage phagocytic clearance of apoptotic PMNs in patients with SLE and healthy controls; to evaluate whether in vitro PMN and macrophage apoptosis and secondary necrosis, and the ability of macrophages to phagocytose apoptotic bodies, are correlated with lupus disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
249
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(265 citation statements)
references
References 49 publications
13
249
1
2
Order By: Relevance
“…20,30 The excess of lymphocyte apoptosis and deficient phagocyte-mediated clearance of apoptotic cells could contribute to B-cell hyperactivity and subsequent autoantibodies overproduction. [9][10]12 Taken together, these findings suggest that molecular mechanisms regulating FasL gene expression are crucial to SLE autoimmunity. The inducible regions of the human FasL promoter have been mapped by deletion and mutational analysis and include the basic regulatory region between À273 and the transcription start site, a region between À431 and À273 responsible for enhanced regulatory transcription, a negative regulatory region between À473 and À900, and another region from À900 to À1200 possibly responsible for enhanced regulatory transcription.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…20,30 The excess of lymphocyte apoptosis and deficient phagocyte-mediated clearance of apoptotic cells could contribute to B-cell hyperactivity and subsequent autoantibodies overproduction. [9][10]12 Taken together, these findings suggest that molecular mechanisms regulating FasL gene expression are crucial to SLE autoimmunity. The inducible regions of the human FasL promoter have been mapped by deletion and mutational analysis and include the basic regulatory region between À273 and the transcription start site, a region between À431 and À273 responsible for enhanced regulatory transcription, a negative regulatory region between À473 and À900, and another region from À900 to À1200 possibly responsible for enhanced regulatory transcription.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, altered monocyte phenotypes and neutropenia lead to impaired recognition and clearance of apoptotic cells, and correlate with anti-dsDNA and disease activity. 6,[9][10][11] Fas ligand (FasL), a trimeric type II membrane protein, belongs to the TNF receptor family that induces apoptosis of cells bearing Fas receptor. 12 Observations in mouse models of SLE demonstrated that mice with Fas (MRL/lpr) or FasL (gld) mutations developed lymphadenopathy with accumulation of CD4ÀCD8À double negative lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…All SLE patients had active disease, and their mean score on the SLE Disease Activity Index (SLEDAI) (32) was 17 (range [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. SLE patients had a mean C-reactive protein (CRP) level of 5.7 mg/liter, and a mean erythrocyte sedimentation rate (ESR) of 40 mm/hour.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, this accelerated apoptosis of monocytes is associated with the formation of autoantibodies and with organ damage (18,19). Second, a clearance deficiency of monocytes and macrophages causes accumulation of apoptotic bodies in different tissue types (20,21). Third, some monocytes become professional antigen-presenting cells upon stimulation with IFN␣ and may present processed antigens of ingested apoptotic cells and nucleosomes to CD4ϩ T cells that subsequently become activated (22).…”
mentioning
confidence: 99%
“…Immune homeostasis and maintenance of immune tolerance are dependent on apoptosis induction and rapid clearance of apoptotic cells in peripheral and central lymphoid organs (40). Autoimmune disease arise from either defective elimination of autoreactive T or B cells, resulting in tissue destruction, or from defective clearance of apoptotic cells displaying autoantigen on their cell surface as in the case of Systemic Lupus Erythematosis (SLE) subjects (41). The BH-3 only protein Bim dependent apoptosis constitutes a critical barrier to autoimmunity.…”
Section: Apoptosis and Human Diseasementioning
confidence: 99%